Therapeutic mobility and breast cancer in France: Experiences of African women - Louise Ludet; Luis Teixeira; Gaëtan des Guetz; Clémence Schantz; Moufalilou Aboubakar; Myriam Baron; Emmanuel Bonnet; Fanny Chabrol; Abdourahmane Coulibaly; Justin Lewis Denakpo; Annabel Desgrées du Loû; Gaëtan Des Guetz; et al. (Elsevier, 2023)
While breast cancer is the most common cancer globally, not all women have access to quality care. Long considered a disease of high-income countries, low- and middle-income countries are now facing a major public health issue regarding cancer. This is the case in sub-Saharan Africa, where access to quality breast cancer treatment is often lacking. This context leads some women to travel abroad, particularly to France, hoping to save their lives. This article aims to examine the experiences, the social cost and the perceptions associated with therapeutic mobility for breast cancer in France. To this end, this study uses a qualitative method based on nineteen biographical interviews with women from sub-Saharan Africa with breast cancer who have migrated to France seeking for treatment. It shows that these women often face significant difficulties throughout their care and life paths in France. Main issues lay in accessing care, housing insecurity, loneliness, and administrative instability. This reflects how the double biographical disruption, caused by cancer and migration, impact entire disease trajectories, from entry to care to post-breast cancer period. With this research, we suggest extending the concept of social death to the issue of women who have undergone therapeutic mobility for their breast cancer in France. Highlighting the experiences of women who remain almost invisible in the public arena, this article analyses poorly heard realities and shows how social inequalities in health can be found even in reconstructing oneself after breast cancer.